Prematurity, hypogammaglobulinemia, and neuropathology with human immunodeficiency virus (HIV) infection. - Pahwa, R (1987)
Infection with the human immunodeficiency virus (HIV) is characteristically associated with hypergammaglobulinemia in both adult and pediatric cases. We report herein four infants who had an HIV infection in association with severe hypogammaglobulinemia and did not exhibit antibodies against HIV. HIV was isolated antemortem or postmortem in all four infants from either peripheral blood, cerebrospinal fluid, or body tissues. HIV infection could be presumed to be acquired transplacentally in two infants and by way of infected blood transfusions during the neonatal period in the other two. Each infant became symptomatic within the first year of life and developed rapidly progressive manifestations of the disease. Features that were common to all four infants include premature birth, failure to thrive, hepatomegaly, and progressive neurological abnormalities that were associated with intracranial calcifications. We concluded that, when infection occurs early in development either by transplacental exposure to the virus or from blood transfusion in small premature infants, hypogammaglobulinemia and deficiency of antibody production leading to the absence of antibody responses on which diagnosis is usually based can occur. Furthermore, progressive central nervous system disease may be a frequent finding in such infants, and this may lead to cerebral calcifications that must be attributed to the HIV infection itself and not to complicating infections--e.g., toxoplasmosis. It is suggested that patients with hypogammaglobulinemia, antibody deficiency syndrome, and central nervous system disease have an extremely bad prognosis.